Theory of Planned Behavior Development Model to Compliance Behavior in Vap Prevention at ICU - Kusnanto, Kusnanto; Suadyani, I Ketut; Wahyuni, Erna Dwi; Arifin, Hidayat (Jurnal Keperawatan Soedirman, 2020)
Background: Ventilator-Associated Pneumonia (VAP) was the leading cause of death in Healthcare-Associated Infections (HCAI) requiring treatment in its specific prevention. Prevention of VAP had not been done optimally, such as nurses had not done hand hygiene and oral care according to procedure, head elevation not yet done as indicated. Purpose: applying Theory of Planned Behavior to nurse compliance behavior to prevent VAP case in ICU of Catholic Hospital Surabaya. Methods: The study was explanative observational with cross-sectional approach. The population was associate nurses working in the ICU and obtained 30 sample with total sampling. The research variables were general attitude, age, education, experience, knowledge, attitude toward VAP, subjective norm, perception to control, intention, preventive compliance behaviour VAP. Instruments in the form of questionnaires and observations. Data analyzed using bivariate Chi-Square (p<0,05) and Partial Least Square. Results: The results showed that: 1) attitudes, age and experience were associated with intentional support factors (p <0.05), while education and knowledge were not related to intentional support factors 2) intentional support factors related to intention (p <0, 05) 3) Intention related to VAP prevention compliance behavior (p <0.05). Conclusion: Nurse compliance behavior in VAP prevention consider their background factor, support factor of intention, and intention.